P1802EVALUATION OF THE GENETICAL FEATURES AFFECTING THE RENAL OUTCOMES IN CHILDREN WITH STEROID RESISTANT NEPHROTIC SYNDROME. (6th June 2020) - Comak, Elif; Toylu, Aslı; Bilge, Ugur; Kaya Aksoy, Gülsah; Koyun, Mustafa; Akman, Sema
Abstract: Background and Aims: Nephrotic syndrome in childhood is characterized by proteinuria, hypoalbuminemia, edema, and hyperlipidemia. Although most children respond to glucocorticoid therapy, approximately 10% of patients turn out to be steroid resistant (steroid-resistant nephrotic syndrome [SRNS]). Although several studies in children with SRNS have shown that mutations in genes encoding proteins in the podocyte skeleton may be responsible for the etiology in only one-third of cases, the genetic features related with renal prognosis and response to immunosuppressive agents are not fully recognized. The aim of this study was to investigate the genomic alterations associated with renal prognosis and resistance to immunosuppression in children with SRNS. Method: The children with SRNS were enrolled in this study. Custom gene panel was designed for next-generation sequencing analysis of more than 20 target genes (ABCB1, ABCC2, CTLA4, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP3A4, CYP3A5, FOXP3, GSTP1, IMPDH1, IMPDH2, NOS3, NR3C1, SLCO1B1, SLCO1B3, TPMT, UGT1A9, UGT2B7) and 200 single nucleotide variants (SNVs) which were reported as implicated in renal prognosis of nephrotic syndrome. The target gene panel was enriched for drug metabolism regulating transporters and enzymes. Results: A total of 25 children, 16 boys (64%), median age at last visit 17.5 years (13-18 years), median age at diagnosis 7.5 years (2-15), median follow-up 9.58±4.54 years, were included in the study. All patients were diagnosed focal segmental glomerulosclerosis on renal biopsy.